2022
DOI: 10.1097/qai.0000000000003085
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Epidemiologic Characteristics of a Cohort of HIV-Infected Mother–Infant Pairs During 21 Years

Abstract: Background: HIV infection continues to be a worldwide public health problem. After the introduction of effective preventive measures, perinatal transmission dramatically decreased. Our aim was to assess the sociodemographic changes in pregnant women living with HIV infection and trends in perinatal transmission rates over time. Setting:The Madrid cohort of HIV-infected mother-infant pairs is a multicenter, prospective, observational, and cohort study that collects information on HIV-infected pregnant women and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The Madrid Cohort of HIV-infected mother-infant pair, which collects prospectively data on women living with HIV (mostly infected by sexual transmission) and their infants, recently reported that the percentage of women suppressed at conception increased from 2000 to 2020 from 49.8% to 73,4%. 29 Overall, our results suggest that intensive efforts during pregnancy can lead to higher rates of viral suppression at delivery.…”
Section: Discussionmentioning
confidence: 63%
“…The Madrid Cohort of HIV-infected mother-infant pair, which collects prospectively data on women living with HIV (mostly infected by sexual transmission) and their infants, recently reported that the percentage of women suppressed at conception increased from 2000 to 2020 from 49.8% to 73,4%. 29 Overall, our results suggest that intensive efforts during pregnancy can lead to higher rates of viral suppression at delivery.…”
Section: Discussionmentioning
confidence: 63%